Freudenthal triple classification of three-qubit entanglement - Borsten,L; Dahanayake,D; Duff,MJ; Rubens,W; Ebrahim,H (Physical Review A, 2009)
We show that the three-qubit entanglement classes, (0) null, (1) separable A−B−C, (2a) biseparable A−BC, (2b) biseparable B−CA, (2c) biseparable C−AB, (3) W, and (4) Greenberger-Horne-Zeilinger, correspond respectively to ranks 0, 1, 2a, 2b, 2c, 3, and 4 of a Freudenthal triple system defined over the Jordan algebra C⊕C⊕C. We also compute the corresponding stochastic local operations and classical communication orbits.